Socio-demographic factors associated with HIV prevalence among pregnant women attending antenatal clinics in six Southern States of India: Evidences from the latest round of HIV sentinel surveillance - Santhakumar Aridoss; Nagaraj Jaganathasamy; Arvind Kumar; Manikandan Natesan; Rajatashuvra Adhikary; Elangovan Arumugam (Wolters Kluwer Medknow Publications, 2020)
Background: HIV/AIDS is a global public health issue and its transmission in a defined geographic region is influenced by the interplay of sociodemographic and behavioral factors. Better understanding of sociodemographic characteristics of HIV-positive individuals is required to prevent the spread of HIV among the general population. Objectives: The objective of the study was to find the association between HIV prevalence and sociodemographic characteristics of pregnant women aged 15-49 years attending the antenatal clinics (ANCs) in six Southern states of India. Methods: The data from the latest round of HIV sentinel surveillance, a cross-sectional study, conducted during January-March 2017 among ANC attendees were considered for this analysis. Blood samples along with other relevant information were collected from 98,634 pregnant women from 248 sites across the states. The association between HIV prevalence and sociodemographic variables was examined using multivariable logistic regression. Results: The highest HIV prevalence was reported in Karnataka (0.38%) and Andhra Pradesh (0.38%), followed by Telangana (0.33%), Odisha (0.28%), Tamil Nadu (0.27%), and Kerala (0.05%). In all states, the prevalence was highest among illiterate pregnant women exception being Kerala, wherein the prevalence was highest in pregnant women with schooling up to primary education. A significant association was found between HIV prevalence and spouse occupation in Karnataka and Odisha and spouse migration in Andhra Pradesh and Karnataka. Conclusions: Need for improvising the interventions for the young, illiterates, having a migrant spouse, and spouse occupation as truckers/hotel staff is recommended to the stakeholders involved in HIV management of the six southern states of India.